Content development and validation for a mobile application designed to train family caregivers in the use of music to support care of people living with dementia - Thompson, Zara; Tamplin, Jeanette; Vieira Sousa, Tanara; Carrasco, Romina; Flynn, Libby; Lamb, Karen E.; Lampit, Amit; Lautenschlager, Nicola T.; McMahon, Kate; Waycott, Jenny; Vogel, Adam P.; Woodward-Kron, Robyn; et al. (Frontiers in Medicine, 2023)
Background Music therapy is increasingly recognized as an effective support for people living with dementia. However, with incidences of dementia increasing, and limited availability of music therapists, there is a need for affordable and accessible ways that caregivers can learn to use music-therapy based strategies to support the people they care for. The MATCH project aims to address this by creating a mobile application that can train family caregivers in the use of music to support people living with dementia. Methods This study details the development and validation of training material for the MATCH mobile application. Training modules developed based on existing research were assessed by 10 experienced music therapist clinician-researchers, and seven family caregivers who had previously completed personalized training in music therapy strategies via the HOMESIDE project. Participants reviewed the content and scored each training module based on content (music therapists) and face (caregivers) validity scales. Descriptive statistics were used to calculate scores on the scales, while thematic analysis was used to analyze short-answer feedback. Results Participants scored the content as valid and relevant, however, they provided additional suggestions for improvement via short-answer feedback. Conclusion The content developed for the MATCH application is valid and will be trailed by family caregivers and people living with dementia in a future study.